How do intestinal probiotics restore the intestinal barrier? - Gou, Hong-Zhong; Zhang, Yu-Lin; Ren, Long-Fei; Li, Zhen-Jiao; Zhang, Lei (Frontiers in Microbiology, 2022)
The intestinal barrier is a structure that prevents harmful substances, such as bacteria and endotoxins, from penetrating the intestinal wall and entering human tissues, organs, and microcirculation. It can separate colonizing microbes from systemic tissues and prevent the invasion of pathogenic bacteria. Pathological conditions such as shock, trauma, stress, and inflammation damage the intestinal barrier to varying degrees, aggravating the primary disease. Intestinal probiotics are a type of active microorganisms beneficial to the health of the host and an essential element of human health. Reportedly, intestinal probiotics can affect the renewal of intestinal epithelial cells, and also make cell connections closer, increase the production of tight junction proteins and mucins, promote the development of the immune system, regulate the release of intestinal antimicrobial peptides, compete with pathogenic bacteria for nutrients and living space, and interact with the host and intestinal commensal flora to restore the intestinal barrier. In this review, we provide a comprehensive overview of how intestinal probiotics restore the intestinal barrier to provide new ideas for treating intestinal injury-related diseases.